Flexible assembled tactile sensor with freely integration design. (1st October 2022) - Yang, Lina; Li, Yang; Wang, Haicheng; Wei, Shan; Li, Zhongli; Liu, Yijian; Chen, Da; Guo, Qiuquan; Sun, Xun
Abstract: Flexible touch-sensing devices have become increasingly multifunctional in wearable interaction electronics owing to the diversification of material synthesis and the flexibility in the structure design. Especially, the latter provides capabilities for the existing sensors owning the common materials with new possibilities to acquire certain requisite functions. Herein, we designed a strain sensor by assembling the nature rubber (NR) substrate with the MoS2 /MWCNT conducting network structure. For demonstrating the flexibility of the proposed integrated model under the application of NR, practical applications were exhibited. The bendable biomimetic hair sensor is integrated into the smart car for robotic tactile to imitate the manner of mammals when sensing the surroundings. Besides, a flexible sensing array can be designed into arbitrary shapes according to users' requirements manifesting its flexibility and practicability. What is more, the sensor used as electronic skin (e-skin) can realize tactile sensing and meanwhile monitor human body movements. The success of this study paves the way for extending this technology to tactile sensing which is a promising lead to develop multifunctional strain sensors for widespread applications.